Aspects associated with smoking and health effects (Research, Society and Development, 2021)
The habit of smoking - smoking, is associated with the development of a series of diseases. It has been common since the dawn of human prehistory. The present study carried out an integrative literature review to gather aspects associated with smoking and the effects on health. An integrative literature review was carried out based on original studies obtained from the SciELO, Google Scholar and LILACS databases. The term "cigarette" refers to a cigarette made from tobacco, although it is used to designate other similar products. Smoking is no longer synonymous only with the consumption of conventional cigarettes made from tobacco. Other products such as the organic tobacco used to make the cigar, the hookah and the electronic cigarette compete for place with the packs. All tobacco derivatives, which can be used in the forms of inhalation (cigarette, cigar, pipe, hookah, straw, electronic cigarette), aspiration (snuff) and chewing (roll smoke), are harmful to health. It is very important to monitor smoking initiation, especially among young people, as this is a preventable action.